Colocalization of pain and reduced intraepidermal nerve fiber density in individuals with HIV-associated sensory neuropathy. (November 2019) - Patel, Imraan G.; Kamerman, Peter R.
Abstract: Introduction: There is poor correlation between decreases in intraepidermal nerve fiber density (IENFD) and the presence of pain in HIV-associated sensory neuropathy (HIV-SN) and other painful distal symmetrical polyneuropathies. Objectives: We investigated whether in individuals with HIV-SN, having pain at the ankle skin biopsy site was associated with lower IENFD compared to when there was no pain at the ankle biopsy site. Methods: We recruited 15 individuals with symptomatic HIV-SN. Nine had pain at the site where the ankle biopsy was taken, whereas 6 did not. Skin punch biopsies for IENFD quantification were taken from the ankle and the thigh. Contrasts between the 2 groups were made using the overlap of confidence interval (CI) method. Results: Intraepidermal nerve fiber density was substantially lower in the group that had pain at the site of the ankle biopsy compared with the other group (6.6 [CI: 5.3–7.2] vs 3.3 [CI: 10.0–15.0] fibers/mm). However, there was no group differences at the thigh biopsy site (15.6 [CI: 15.0–15.9] vs 16.2 [CI: 14.5–17.8] fibers/mm). When taking the ratio of ankle IENFD:thigh IENFD, the point estimate for the pain at the ankle group (0.43 [CI: 0.36–0.48]) was about half that of the other group (0.81 [CI: 0.68–0.87]). Conclusion: Thus, colocalization of pain to the ankle is associated with meaningful decreases in ankle IENFD. Abstract : Supplemental Digital Content is Available in the Text.